Effects of magnesium on the microstructure and properties of Al–Si alloy deposited by wire and arc-based additive manufacturing. (10th November 2021) - Li, Chengde; Gu, Huimin; Wang, Wei; Wang, Shuai; Ren, Lingling; Wang, Zhenbiao; Ming, Zhu; Zhai, Yuchun
ABSTRACT: The effects of Mg on microstructure, defects and properties of Al–Si alloy deposited by Wire and Arc-based Additive Manufacturing (WAAM) were investigated. The WAAM alloys were characterised by the metallographic microscope, X-ray diffraction, scanning electron microscope, computed tomography and electronic universal testing machine. The results show that the secondary dendrite arm spacing (SDAS) and hydrogen content of as-deposited WAAM alloy increase, and the tendency of pore formation increases with an increase in Mg content. The impurity Fe in the WAAM alloy with low Mg content is mainly in β-Fe phase, while with high Mg content is mainly in the π-Fe phase. After solution treating and ageing treatment (T6 heat-treat), the microstructure of WAAM alloy tends to be uniform. With the increase of Mg content, the size of eutectic silicon particles increases gradually. Furthermore, the UTS and YS of the alloys increased, and the elongation decreased.